CHEMICAL CHARACTERISTICS OF PYROLYSIS LIQUID SMOKE SOME TYPES OF WOODSMOKE - Juwita S; Bustari Hassan; Tjipto Leksono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Liquid smoke can be used to preserve and add to the taste of food. The quality of liquid smoke is determined by the type of wood smoke used. This study aimed to evaluate the yield and chemical composition of the liquid smoke made from wood kandis, wood Laban, Ubar wood and coconut shell. The fourth type of timber is made of liquid smoke with condensation method using a pyrolysis. Parameters danalisis consists of the chemical composition of wood, the yield of liquid smoke, phenols, acids, pH, carbonyl and antioxidants. The results showed that wood Laban has a higher value on the total carbonyl is 15:43% and the value of the antioxidant is 84.26%.Keywords: Liquid Smoke, preserve, wood Laban, total carbonyls, antioxidants.